Effects of an Online Self-Assessment Tool on Teachers' Digital Competencies - Giovanni Abbiati; Davide Azzolini; Anja Balanskat; Katja Engelhart; Daniela Piazzalunga; Enrico Rettore; Patricia Wastiau (Institute of Labor Economics (IZA), 2023)
We evaluate the effects of an online self-assessment tool on teachers' competencies and beliefs about ICT in education. The causal impact of the tool is evaluated through a randomized encouragement design, involving 7,391 lower secondary teachers across 11 European countries. Short-run impact estimates show that the use of the tool led teachers to critically revise their technology-enhanced teaching competencies (-0.14 standard deviations) and their beliefs about ICT in education (-0.35 s.d.), while there is no impact on their probability of taking specific training. The effects are concentrated among teachers in the top-end tail of the distribution of pre-treatment outcomes. We provide suggestive evidence that the feedback score provided by the tool triggered such results by providing a negative information shock.
Keywords: I21; C93; 330; ICT; technology-enhanced teaching; self-assessed competencies; experimental design; teaching practices